The walls have eyes : surviving migration in the age of artificial intelligence - Molnar, Petra (Lawyer); Achiume, E. Tendayi (New York : The New Press, 2024)
"An expose of the inhumane and lucrative sharpening of borders around the globe through experimental surveillance technology"--
Foreword -- Author's note -- Introduction -- 1. "The wall bleeds rust" : robo-dogs in the Sonoran Desert -- 2. "Smart borders kill" : technological violence at the fringes of Europe -- 3. "If we go there, we will go crazy" : refugee camps as digital prisons -- 4. "Recognizing liars" : AI lie detectors, voice printing, and digital incarceration -- 5. "Data is the new oil" : the silicon savanna and data colonialism in East Africa -- 6. "All roads lead to Jerusalem" : a lucrative border industrial complex -- 7. The politics of exclusion and fear -- 8. Strategies of resistance -- Afterword -- Acknowledgments -- Reading list for uncertain times -- Notes.
"Foreword by E. Tendayi Achiume"--PDF image of copyright page.
Includes bibliographical references.
Online resource; title from PDF title page (ProQuest Ebook Central, viewed on August 20, 2024).
JSTOR
Keywords: Border security -- Technological innovations; Emigration and immigration -- Technological innovations; Artificial intelligence -- Political aspects; Diplomacy; International relations; Social sciences; Electronic books; Sécurité frontalière -- Innovations; Émigration et immigration -- Innovations; Intelligence artificielle -- Aspect politique; Diplomatie; Relations internationales; Sciences sociales; Livres numériques.; diplomacy; international relations; social sciences; e-books.; Emigration & Immigration; LAW; Diplomacy; International Relations; POLITICAL SCIENCE; Security (National & International); SOCIAL SCIENCE; POLITICAL SCIENCE / Public Policy / Immigration; Electronic books